Ideas and the Politics of School Choice Policy: Portfolio Management in Philadelphia. Issue 1 (January 2020) - Quinn, Rand; Ogburn, Laura
We examine the role of ideas in the politics of school choice policy and situate our study within scholarship that understands frames and logics as types of ideas operating in the foreground and background of policy debates. Our data are from a case study of political contention over portfolio management reform (in which a central office oversees a network of schools operating under varying forms of governance) in Philadelphia, Pennsylvania. We find that frames and counterframes deployed by stakeholders are resonant with societal-level logics of community localism, market transaction, and state bureaucratic administration. For proponents of portfolio reform, diagnostic frames are drawn from logics of community and state, while prognostic frames are resonant with a market logic. For opponents, the association is flipped: diagnostic counterframes challenge a market logic, and logics of community and state inform prognostic counterframes. Our study demonstrates how ideational processes shape political contention in education reform.